2019
DOI: 10.1093/ageing/afz005
|View full text |Cite
|
Sign up to set email alerts
|

Should we provide outreach rehabilitation to very old people living in Nursing Care Facilities after a hip fracture? A randomised controlled trial

Abstract: Objective to determine whether a 4-week postoperative rehabilitation program delivered in Nursing Care Facilities (NCFs) would improve quality of life and mobility compared with receiving usual care. Design parallel randomised controlled trial with integrated health economic study. Setting NCFs, in Adelaide South Australia. Subjects people aged 70 years and older who were recovering from hip fracture surgery and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…People who have suffered fractures tend to limit their daily activities and simultaneously experience negative emotions such as depression, anxiety and decreased self-confidence. The FOF reduces flexibility, independence and balance of the body, thereby increasing the risk of falls [44,45]. We also found that the more chronic health disorders postmenopausal women have, the more likely they are to fall.…”
Section: Medical Risk Factorsmentioning
confidence: 53%
“…People who have suffered fractures tend to limit their daily activities and simultaneously experience negative emotions such as depression, anxiety and decreased self-confidence. The FOF reduces flexibility, independence and balance of the body, thereby increasing the risk of falls [44,45]. We also found that the more chronic health disorders postmenopausal women have, the more likely they are to fall.…”
Section: Medical Risk Factorsmentioning
confidence: 53%
“…3 Despite dementia being common among older people with hip fracture and that the population has complex care needs, 6 the condition has often been an exclusion criterion for participation in previous clinical trials. 8 There is, however, growing evidence that people with hip fracture and cognitive impairment (CI) or dementia benefit from enhanced interdisciplinary rehabilitation in hospital, 9,10 combined in-hospital and in-home rehabilitation, [11][12][13][14] and from rehabilitation in nursing homes, 15 although the optimal rehabilitation strategies remain unclear. 6 To our knowledge, no previous team-based home rehabilitation (HR) interventions after hip fracture have included people with severe CI or dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest nursing home residents who had multiple co-morbidities and marked dementia appeared to respond favourably to medical and allied health intervention in this current study, at least while the rehabilitation was ongoing. However, once the rehabilitation was withdrawn at 4 weeks, their risk for death increased [4]. The combined medical, physiotherapy and dietetic interventions did reduce early mortality, but it is not known whether an extended program may have promoted sustained mortality benefits and ongoing functional improvements.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse events were able to be classified in four main categories: Falls, Skin tears/wounds, Medical (Chest infection/pneumonia) and Medical (other). Mortality and re-fracture rates data has already been reported in the main study publication [4] . Falls were the most commonly reported adverse event (n = 258), with those receiving the addition of in-reach rehabilitation incurring 62.7% of the falls, with 12 people (21%) requiring hospital admission and three people sustaining hip fractures.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation